Resident perceptions of Competency-Based Medical Education - Mann, Steve; Hastings Truelove, Amber; Beesley, Theresa; Howden, Stella; Egan, Rylan (Canadian Medical Education Journal, 2020)
Background: Residency training programs in Canada are undergoing a mandated transition to competency-based medical education (CBME). There is limited literature regarding resident perspectives on CBME. As upper year residents act as mentors and assessors for incoming cohorts, and are themselves key stakeholders in this educational transition, it is important to understand how they view CBME. We examined how residents who are not currently enrolled in a competency-based program view that method of training, and what they perceive as potential advantages, disadvantages, and considerations regarding its implementation. Methods: Sixteen residents volunteered to participate in individual semi-structured interviews, with questions focussing on participants’ knowledge of CBME and its implementation. We used a grounded theory approach to develop explanations of how residents perceive CBME. Results: Residents anticipated improved assessment and feedback, earlier identification of residents experiencing difficulties in training, and greater flexibility to pursue self-identified educational needs. Disadvantages included logistical issues surrounding CBME implementation, ability of attending physicians to deliver CBME-appropriate feedback, and the possibility of assessment fatigue. Clear, detailed communication and channels for resident feedback were key considerations regarding implementation. Conclusions: Resident views align with educational experts regarding the practical challenges of implementation. Expectations of improved assessment and feedback highlight the need for both residents and attending physicians to be equipped in these domains. Consequently, faculty development and clear communication will be crucial aspects of successful transitioning to CBME.